Study Visual Functions in Epileptic Patients using Depakote - H, Natissiyan; L, Sohheilmaneshi; A, Naradini (Journal of Ophthalmology and Research, 2019)
Depakote (divalproex sodium) is combined of valproic acid and sodium valproate used to treat bipolar disorders, epilepsy and migraine. Side effects of Depakote include weakness, tremor, drowsiness, diarrhea, vomiting, nausea, changes in menstrual periods. The aim of this study is to find if this drug has side effects on the retina. Materials and Methods: 18 patients suffering from epilepsy with no history of visual complaints were included in the study. They all take Depakote as a medication of treatment epilepsy for at least nine months. Also 18 subjects without such prescription were enrolled as a control group. The VEP and ERG obtained in the two groups were compared to find if taking Depakote can affect the eye after a while. Results: The mean voltage of ERG was 87.88 ± 12.08 and 88.16 ± 12.97 μV in case and control groups and the mean latency was 38.2 ± 2.86 and 37.80 ± 3.36 msec in case and control groups (P>0.05) that shows there is no significant difference for ERG parameters in two groups. The mean latency of VEP, P100 peak were 1.9/7.23 and 96/5.37 msec and the mean amplitude were 8 ± 2.83 and 8 ± 2.41 μv in case and control groups. The difference between two groups was significant in latency of VEP but no significant difference in amplitude was shown comparison of two groups. Conclusions: By the result of this research, one can conclude that Depakote can affect on retina of eye in patients taking this drug for at least a few months.